Glial cell response to constant low light exposure in rat retina - Bruera, Manuel G.; Benedetto, María M.; Guido, Mario E.; Degano, Alicia L.; Contin, María A. (Visual neuroscience, 2022)
To study the macroglia and microglia and the immune role in long-time light exposure in rat eyes, we performed glial cell characterization along the time-course of retinal degeneration induced by chronic exposure to low-intensity light. Animals were exposed to light for periods of 2, 4, 6, or 8 days, and the retinal glial response was evaluated by immunohistochemistry, western blot and real-time reverse transcription polymerase chain reaction. Retinal cells presented an increased expression of the macroglia marker GFAP, as well as increased mRNA levels of microglia markers Iba1 and CD68 after 6 days. Also, at this time-point, we found a higher number of Iba1-positive cells in the outer nuclear layer area; moreover, these cells showed the characteristic activated-microglia morphology. The expression levels of immune mediators TNF, IL-6, and chemokines CX3CR1 and CCL2 were also significantly increased after 6 days. All the events of glial activation occurred after 5–6 days of constant light exposure, when the number of photoreceptor cells has already decreased significantly. Herein, we demonstrated that glial and immune activation are secondary to neurodegeneration; in this scenario, our results suggest that photoreceptor death is an early event that occurs independently of glial-derived immune responses.